Pengaruh Senam Hipertensi Terhadap Perubahan Tekanan Darah Pada Lansia Dengan Hipertensi di Posbindu Pujasuma Kelurahan SP VI Sari Bungamas Tahun 2022: The Effect of Hypertension Exercise on Changes in Blood Pressure in Elderly People with Hypertension at Posbindu Pujasuma, SP VI Sari Bungamas Village, 2022 - Hartati, Sri; Kamesyworo; Elviani, Yeni; Haryanti, Eka (Chakra Brahmanda Lentera Institute, 2023)
The Elderly is the final stage of development in human life, the elderly are very susceptible to various diseases, one of which is hypertension. Hypertension or high blood pressure is often said to be the silent killer because it is a deadly disease that is not accompanied by early symptoms. Hypertension gymnastics is a sport that aims to increase the flow of blood and oxygen into the active muscles and skeleton, especially the heart muscle. This study aims to determine the effect of hypertension exercise on changes in blood pressure in the elderly with hypertension at Posbindu Pujasuma Kelurahan SP VI Sari Bungamas in 2022. This study used a pre-experimental design with one group pretend est posttest design. The number of samples is 50 respondents. The population of this stwaswere all elderly people at Posbindu Pujasuma Kelurahan SP VI using a purposive sampling technique. Data collection techniques used tensimeters andobservation sheets, while data analysis used the Wilcoxon Signed Rank Test. The results of the study were obtained before the treatment the average systolic blood pressure was 171.60 mmHg after the treatment the average systolic blood pressure was 146.80 mmHg. And the results before the treatment mean diastolic blood pressure was 109.20 mmHg after treatment the average was 92.60 mmHg. The results of data analysis using the Wilcoxon Rank Test obtained statistically significant results of 0.000 less than the significant level of 5% (ρ–value = 0.000 <0.05) that there is a significant effect of hypertension exercise on changes in blood pressure in the elderly with hypertension at Posbindu Pusjasuma Pusjasuma SP VI Lahat in 2022. For this reason, it is hoped that cadres and health workers can provide counseling about hypertension exercises, and the elderly to do hypertension exercises regularly so that they can reduce hypertension. Keywords: Hypertension Exercise, Elderly, Changes in Blood Pressure.